PENGARUH JENIS SEDIMEN WETLAND DALAM REDUKSI SULFAT PADA LIMBAH AIR ASAM TAMBANG (AAT) - Fahruddin, Fahruddin (Jurnal Teknologi Lingkungan, 2009)
Increasing mining activities in several regions in Indonesia, began to faceproblems, namely of environmental pollution. One of the mining waste that is liquidsulfur, or acid mine water, which can lower the pH of the water and dissolves heavymetals. Countermeasures for the chemical method is to use lime, but this is lesseffective. The method is good and is environmentally friendly way by using biologicalbacteria sulphate reduction bacteria (SRB) that naturally there are many in thesediment wetland. Goal of this research is to find the type of sediment wetland mosteffectively increase the pH and decrease the concentration of sulphate in acid minewater. The sediment wetland is used mangroves, swamp, rice fields, and beaches.Treatment bioreaktor made on the filled with sediment underneath the compost isgiven further incubation for 50 days. The observation of pH and content of sulphatebased on the value of OD spektrofotometer and known pH increased to the highestin the pH of 7.3 is in the swamp sediment treatment, while the only other treatmentuntil the pH 6-6,7. Increasing the pH in accordance with the decrease in the rate ofSO4 is most sharply in the swamp sediment treatment as well as the most effectivetreatment.